2006
DOI: 10.2190/b3kl-ryu6-9pgu-5rmn
|View full text |Cite
|
Sign up to set email alerts
|

State Anxiety during Watchful Waiting for Urinary Lithiasis

Abstract: Clinicians should be more flexible when they face the above group of patients, as far as the duration of watchful waiting period is concerned, because a long waiting sets those patients under significant emotional burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
(17 reference statements)
0
12
0
1
Order By: Relevance
“…18 Whether a stone of 4 mm can cause similar renal functional impairment and subsequently necessitates formal initial and follow-up renal impairment studies is unknown. 18 Taking into consideration that watchful waiting for ureteral stones <5 mm in diameter may significantly increase the patient's state of anxiety, 25 individual preferences after a thorough counseling about treatment choices, degree of invasiveness, and spectrum of complications will guide urologists and patients to select the best treatment option. 26 …”
Section: Symptomatic Stones Of Small Diametermentioning
confidence: 99%
“…18 Whether a stone of 4 mm can cause similar renal functional impairment and subsequently necessitates formal initial and follow-up renal impairment studies is unknown. 18 Taking into consideration that watchful waiting for ureteral stones <5 mm in diameter may significantly increase the patient's state of anxiety, 25 individual preferences after a thorough counseling about treatment choices, degree of invasiveness, and spectrum of complications will guide urologists and patients to select the best treatment option. 26 …”
Section: Symptomatic Stones Of Small Diametermentioning
confidence: 99%
“…Wartezeit bedeutet primär ein erzwungenes Stillstehen und vermittelt schnell ein Gefühl von Ohnmacht und Hilflosigkeit, ein "Sich-ausgeliefert-Fühlen". Dies wiederum kann die Möglichkeiten eines Patienten, sich effektiv mit dem Thema Narkose auseinanderzusetzen, reduzieren [20]. Meist wird Wartezeit aber nur dann als belastend empfunden, wenn sie den Betreffenden zur Untätigkeit zwingt.…”
Section: Kurze Wartezeit/prämedikationsortunclassified
“…Two studies reported associations between anxiety and the number of painful colic episodes in urolithiasis, 13,14 and Diniz et al 13 also reported a positive association between depression and painful colic episodes. In contrast, only 1 study reported no association between psychological distress and urolithiasis, a finding attributed to the inclusion of calcium oxalate (CaOx) stone formers only in the study sample.…”
Section: Psychological Distress and Urolithiasismentioning
confidence: 99%
“…Finally, lower anxiety scores were found in patients who received information from the urologist relating to their treatment and in patients that were not asked by the urologist to partake in the treatment decision-making process (eg, choosing either SWL or URS). 74 Psychological Distress and Watchful Waiting Only 1 study reported on the relationship between psychological distress and watchful waiting for urolithiasis 14 whereby state anxiety was higher for patients at the end of the waiting period, particularly if patients were male, had elevated anxiety scores pre-watchful waiting or if patients reported more than 1 stone-related pain episode in the 30day study period. 14…”
Section: Psychological Distress and Urological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation